Greater trochanteric pain syndrome and gluteus medius and minimus tendinosis: nonsurgical treatment. (January 2018) - Torres, Ana; Fernández-Fairen, Mariano; Sueiro-Fernández, José
Greater trochanteric pain syndrome (GTPS) affects 10–25% of people in developed countries. The underlying etiology for GTPS is most commonly the tendinosis or a tendon tear of the gluteus medius, minimus or both at the greater trochanter; the inflammation of the tendon is not a major feature. We critically evaluated conservative treatment, for which we reviewed 76 publications, grading them according to four levels of evidence. We identified a wide variety of conservative treatment options: home therapy (insoles, walking sticks/crutches, orthotic devices, stretching exercises and preventive measures); physiotherapy (massage and stretching exercises); infiltrations (corticosteroids and local anesthetics); image-guided infiltrations (fluoroscopy and ultrasound); shockwave therapy; platelet-rich plasma injection; and drug therapy. Severe complications associated with infiltrations are extremely rare, as are those associated with shockwave therapy. The most effective treatments were infiltrations with corticosteroids and shockwave therapy. We propose a graded treatment schedule for patients with GTPS.